PENGARUH TERPAAN SALES PROMOTION PADA INSTAGRAM ADS DAN INTENSITAS MEMBACA ONLINE CUSTOMER REVIEW PADA FEMALE DAILY TERHADAP KEPUTUSAN PEMBELIAN TONER AVOSKIN BEAUTY - Neovansa, Azizi; Bayu Widagdo, Muhammad; Luqman, Yanuar (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The consumption trend of beauty products in Indonesia has highlighted toner as one of the daily skincare essentials. Local skincare brands, including Avoskin Beauty, which was once the top toner brand in 2022, have been actively promoting their products. Avoskin employed an Instagram Ads sales promotion strategy. Additionally, Female Beauty is recognized as the leading beauty forum and community, serving as a primary information source for consumers before making purchases. However, Avoskin's toner sales experienced a significant decline in 2023. This study aims to investigate the influence of Instagram Ads sales promotion exposure (X1) and the intensity of reading online customer reviews on Female Daily (X2) on the purchasing decision of Avoskin Beauty toner (Y). Using the Advertising Exposure theory and simple linear regression analysis, the study found that both sales promotion exposure and the intensity of reading online customer reviews have a positive and significant impact on the purchasing decision of Avoskin Beauty toner